Effects of Nutrients on the Phytoplankton Community Structure in Zhanjiang Bay - Zhen Zeng; Fajin Chen; Qibin Lao; Qingmei Zhu (Journal of Marine Science and Engineering)
With rapid economic and social development, eutrophication in coastal areas is currently one of the most severe environmental problems worldwide. However, our understanding of the response of the phytoplankton community structure to the intensification of coastal eutrophication is still relatively limited. Here, seasonal phytoplankton, environmental factors, and nutrients were investigated in 2009 and 2019 in Zhanjiang Bay, where eutrophication has intensified in recent years, to analyze the variation in nutrient structure and its impact on the phytoplankton community. The results revealed that the DIP and DSI concentrations in 2019 were higher than those in 2009. However, dissolved inorganic nitrogen (DIN) has decreased substantially over the past several decades, which is due mainly to the decrease in anthropogenic nitrogen emissions, the substantial increase in the intrusion of high-salinity seawater, and the high-phosphorus wastewater discharged from urban industries. This resulted in a decrease in phytoplankton cell abundance, phytoplankton composition, and species diversity (H′) in 2019 compared with 2009. In addition, the superior N transport, storage, and response strategy to a low N supply of diatoms, especially Skeletonema and Chaetoceros, might benefit the growth of diatoms under low DIN conditions. The lower DIN/DIP ratio in 2019 favored the growth of diatoms, especially Skeletonema and Chaetoceros, leading diatoms to dominate the phytoplankton assemblage. This study demonstrates how changes in nutrient structure alter the community structure of phytoplankton, providing new insights into deepening our understanding of eco-environmental evolution.